2019
DOI: 10.24090/tarling.v3i1.2031
|View full text |Cite
|
Sign up to set email alerts
|

Manajemen Pengorganisasian Program Bahasa Arab di Pondok Pesantren Salaf

Abstract: Pengorganisasian (organizing) merupakan langkah kedua dalam manajemen organisasi setelah perencanaan (planning). Perencanaan yang matang tidak akan berjalan sempurna, tanpa ada yang menjalankan dan menggerakkan, tanpa diperjelas pekerjaan dan siapa yang akan mengerjakannya. Pengorganisasian yang baik menghasilkan bentukorganisasi yang baik, mulai dari sistem kerja, struktur, sumberdaya hingga aspek lainnya. Penelitian ini membahas tentang: 1) Manajemen pengorganisasian dalam program bahasa Arab Pondok pesantre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Organizing of International Cooperation in Intensive Arabic Course It is an activity to unite the main resources by arranging and organizing human resources in a strategic pattern so that they can carry out useful activities to achieve the desired goals (Hidayati et al 2019). According to G.R Terry, organizing is an activity of connecting the work of each human resource so that they can work together in certain conditions and environments effectively and efficiently in carrying out tasks to achieve the desired goals and objectives (Terry and Winardi 2012:233).…”
Section: Findingmentioning
confidence: 99%
“…Organizing of International Cooperation in Intensive Arabic Course It is an activity to unite the main resources by arranging and organizing human resources in a strategic pattern so that they can carry out useful activities to achieve the desired goals (Hidayati et al 2019). According to G.R Terry, organizing is an activity of connecting the work of each human resource so that they can work together in certain conditions and environments effectively and efficiently in carrying out tasks to achieve the desired goals and objectives (Terry and Winardi 2012:233).…”
Section: Findingmentioning
confidence: 99%
“…While other studies that discuss organizational management in other places differ in focus of discussion, some only infer results on the type of organization, the way of handing over authority and programs There are also groupings that only draw conclusions on the weak organizational structure by mentioning the (Umam et al, 2019)penjababnya (Rahmawati, 2018) , and there are only two things, namely the picture of coordination and division of tasks (Hidayati et al, 2019).…”
Section: Lack Of Line Organizationmentioning
confidence: 99%
“…Previous studies that discussed organizational management aimed to find out how to empower youth through the implementation of youth organization management (Saneba et al, 2021), Organizational management consists of various activities in the form of planning and managing organizational resources to achieve the expected goals, and studies in the management of arabic language education organizations and found organizations that are unclear and there is no clear structure in them and studies look at the management of the organization of the Dar Al-Lughah Arabic language center course program and Islamic Studies (Miftakhul Fariz, 2016) while in markaz Al azhar there is no clear management organization structure (Hidayati et al, 2019), and in ma'had Manbaus shalihin (Umam et al, 2019), the management of the orgasnization of the Arb language there is clear. With the aforementioned background, this study aims to describe organizational management in the Arabic Language Education Study Program in Stiba ar-raayah.…”
Section: Introductionmentioning
confidence: 99%
“…Fitri Hidayati, et al in their research stated that effective governance results in an efficient organizational structure, including in terms of work systems, structures, resources, and other aspects (Hidayati et al 2019). Fathor Rachman, in his research, highlighted that careful planning will not be optimally successful without active and clear implementation, including an understanding of tasks and who is responsible for carrying them out.…”
Section: Introductionmentioning
confidence: 99%